MELON PEEL, ITS CHEMICAL COMPOSITION AND MEDICINAL PROPERTIES - B. B. Norboeva; G.B. Buranova; K.T. Dustov (Journal Park Publishing, 2023)
The article gives the chemical composition, the use of dried melon in the treatment of certain diseases and an opionion on the medicinal properties.
Keywords: dried melon, C, PP vitamin, folic acid, sucar substances, mineral salts, pectin, medicinal properties.